No Complicated Ectopic Pregnancy: Medical Management With Methotrexate In The Maternal Perinatal National Institute - admin, admin (2018)
Objective. To determine the characteristics of medical management with methotrexate in unruptured ectopic pregnancy in Instituto Nacional Materno Perinatal in Lima. Material and methods. A descriptive study, retrospective, realized between January 2009 and December 2010. These were 30 patients diagnosed with unruptured ectopic pregnancy who received methotrexate in the study period. The instrument used was a data collection form developed for study purposes. Results. The most frequent was tubal right at the 56,7% of cases, the most widely used protocol was single-dose in 86,6 % of cases, the most common size was 20 to 35 mm in 60 % of cases, 70 % of cases became negative B-hCG (fraction B of human chorionic gonadotropin), 30% required surgery, the most frequent adverse reaction to methotrexate was nausea (10% of cases).Conclusions. Medical management with methotrexate is an alternative for patients with unruptured ectopic pregnancy, became negative B-hCG (70%). There was no statistically significant differences in the values of the B-hCG at the time of surgical decision.The most widely used protocol was single-dose and route of administration was intramuscularly in all patients.